2014
DOI: 10.1108/ijlls-01-2013-0010
|View full text |Cite
|
Sign up to set email alerts
|

Lesson study incorporating phase-based instruction using Geometer's Sketchpad and its effects on Thai students’ geometric thinking

Abstract: Purpose – Geometry has, in many countries, proved to be one of the problematic topics in mathematics. The purpose of this paper is to report on a study that was carried to investigate the effects of lesson study incorporating phase-based instruction (LS-PBI) using Geometer's Sketchpad (GSP) on Thai students’ geometric thinking. Design/methodology/approach – The effectiveness of the LS-PBI using GSP within the targeted context was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…One of the important features of the Geometer's Sketchpad (GSP) is its effective visualization feature (Adulyasas & Abdul Rahman, 2014). It has been reported, in some studies, that geometric thinking skills related to angles, polygons, 2D and 3D shapes, rotation and rotation skills, and visualization skills have improved by delivering GSPsupported geometry lessons (Adulyasas & Abdul Rahman, 2014;Dixon, 1997;Tieng & Eu, 2014).…”
Section: Geometer's Sketchpadmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the important features of the Geometer's Sketchpad (GSP) is its effective visualization feature (Adulyasas & Abdul Rahman, 2014). It has been reported, in some studies, that geometric thinking skills related to angles, polygons, 2D and 3D shapes, rotation and rotation skills, and visualization skills have improved by delivering GSPsupported geometry lessons (Adulyasas & Abdul Rahman, 2014;Dixon, 1997;Tieng & Eu, 2014).…”
Section: Geometer's Sketchpadmentioning
confidence: 99%
“…One of the important features of the Geometer's Sketchpad (GSP) is its effective visualization feature (Adulyasas & Abdul Rahman, 2014). It has been reported, in some studies, that geometric thinking skills related to angles, polygons, 2D and 3D shapes, rotation and rotation skills, and visualization skills have improved by delivering GSPsupported geometry lessons (Adulyasas & Abdul Rahman, 2014;Dixon, 1997;Tieng & Eu, 2014). It has been noted that one particular study found that cone nets could not be understood with the use of GSP, with teachers instead having to explain them again with concrete models and the paper-folding method (Adulyasas & Abdul Rahman, 2014).…”
Section: Geometer's Sketchpadmentioning
confidence: 99%
See 2 more Smart Citations
“…By learning based on physics problems, students can be empowered to analyze, make quick answers, analyze data, and conclude a certain answer based on the data obtained (Wijnia et al, 2014). It means that problem-based learning can encourage students to think scientifically (Adulyasas & Abdul Rahman, 2014). In addition, it helps students in finding new information, trains collective work skills, and makes students as innovators (Mergendoller et al, 2006).…”
Section: Introductionmentioning
confidence: 99%